HUBUNGAN KUALITAS KOMUNIKASI ORANG TUA DAN PERAN TEMAN SEBAYA DENGAN PERILAKU PENCEGAHAN HIV/AIDS PADA REMAJA DI SMA YAPPENDA KOTA JAKARTA UTARA - Priskillia Marisa Rory (2021)
The quality of parental communication and the role of peers have an important role in shaping the behavior of a teenager in preventing HIV/AIDS. This study aims to determine the relationship between the quality of parental communication and the role of peers with HIV/AIDS prevention behavior in adolescents at SMA YAPPENDA, North Jakarta. The design of this study used a descriptive analytic method with a cross sectional approach. The population in this study were students of SMA YAPPENDA, North Jakarta. The sample in this study was calculated using a purposive sampling technique with a total sample of 208 respondents. The data analysis used was Chi Square test which showed that p-value = 0.003 (p-value <0.05) and the role of peers with HIV/AIDS prevention behavior showed p-value = 0.007 (p-value <0.05). . The conclusion from the results of this study is that there is a relationship between the quality of parental communication and the role of peers with HIV/AIDS prevention behavior in adolescents in SMA YAPPENDA, North Jakarta. Community nurses are expected to create programs that can support smooth communication between adolescents and their parents and increase the role of peers by providing education to the role of peers in order to provide information to their peers.